Analiza ryzyka modelu szacowania rezerw IBNR w zakładzie ubezpieczeniowym : modele stochastyczne dla danych zagregowanych i indywidualnych - Karwański, Marek; Szczęsny, Wiesław (Analysis of Risk of IBNR Reserves Estimating Model in Property-Casualty Insurance : the Comparison of Stochastic Models for Aggregate and Individual Data, 2008)
The accuracy of estimating the IBNR reserves has a very large impact for financial results of an insurance company. In the paper the different methods are compared from the industry standards usually used by actuaries and the methods recommended by international supervisors to models estimated on individual data. The results show that methods for individual data are the best for fitting reserves due to market changes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 116-127